SISTEM INTEGRASI BANK SAMPAH KOTA YOGYAKARTA - Annisaa Utami; Rr Yuliana Rachmawati K; Erfanti Fatkhiyah (Jurnal SCRIPT, 2016)
Trash is still a big problem for Indonesia. Thousands of garbage accumulated daily, ranging from household garbage to the garbage industry. Then there must be a strategy for this, in order to increase the awareness of society towards waste, and can help the performance of the Government in dealing with these problems. One of the solutions that exist namely with the establishment of the bank trash. The Bank is the concept of garbage collection trash is dry and sorted and have management like banking, but that savings is not money but rather rubbish.The system integration of the Bank's Trash is a web-based system. The system is built using the PHP programming language with the CodeIgniter Framework and MySQL databases, data modeling using the Unified Modeling Language (UML). The system uses the concept of multi level user on login consisting of Admins and sysops, equipped with the Google Maps API to display a map to a Web page.So, visitors can view the location of the bank trash through the map, a search based on the name of the bank the bank trash bins and address, showing the form of rubbish, the kind of garbage and turnover in each bank and junk. Admin can perform the processing of user data, the data types of garbage, junk, form data data data districts, subdistricts, and garbage data bank data turnover. Administrators can manage the garbage bank data types of junk, junk, junk prices form, turnover and user.